THREE MODELS FOR ORDERING CONSTITUTIONAL ORDERS - Belov, Martin (Pravni zapisi, 2022)
The article explores constitutional transitions from the viewpoint of three explanatory and ordering paradigms proposed by the author. These are Westphalian constitutionalism, post-Westphalian constitutionalism and neo-Westphalian constitutionalism. The analysis focusses on the crisis of the two main paradigms of Westphalian Modernity – the territoriality of power and the hierarchy having projections on constitutional supremacy and political sovereignty. It explores how these two main forms of Westphalian constitutional geometry are challenged by globalism and neo-regionalism. The paper revolves around the metamorphoses of the pillars of constitutionalism in the context of globalization, as a holistic and universal project that has been unfolding in recent decades, and the current trends toward redefining globalization in terms of global regionalism and post-territorial technocratic governance.